1976
DOI: 10.1029/jc081i030p05401
|View full text |Cite
|
Sign up to set email alerts
|

Nearshore currents off Long Island

Abstract: Some new and interesting current meter observations have recently been reported by Scott and Csanady [1976]. One of their results is the finding of a linear relationship between longshore wind stress and currents observed 2 m above the bottom. Using a frictional model, they are able to draw inferences about the longshore slope of sea level in the absence of wind. The purpose of the present note is to expand on their interpretation of the longshore slope and to offer some cautionary remarks concerning the compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
66
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 11 publications
13
66
0
1
Order By: Relevance
“…Over the inner shelf, the balance tends to be between three terms: along-shelf wind stress and bottom stress and pressure gradient (Scott and Csanady, 1976;Pettigrew, 1981;Lentz and Winant, 1986;Masse, 1988;. In the surfzone, the wave radiation stress gradient again becomes a dominant term and is balanced by bottom stress (Thornton and Guza, 1986;Svendsen and Putrevu, 1994;Feddersen et al, 1998;.…”
Section: Introductionmentioning
confidence: 99%
“…Over the inner shelf, the balance tends to be between three terms: along-shelf wind stress and bottom stress and pressure gradient (Scott and Csanady, 1976;Pettigrew, 1981;Lentz and Winant, 1986;Masse, 1988;. In the surfzone, the wave radiation stress gradient again becomes a dominant term and is balanced by bottom stress (Thornton and Guza, 1986;Svendsen and Putrevu, 1994;Feddersen et al, 1998;.…”
Section: Introductionmentioning
confidence: 99%
“…From the vorticity tendency balance, it was shown that the assumption of vanishing cross-shore transport at all distances from the coast implied a constant longshore pressure gradient. The magnitude of this gradient was viewed as a parameter expressing the influence of the rest of the ocean on the shelf region considered, and was determined from the analysis of observational evidence (Scott and Csanady, 1976). Key features of the observations, such as the presence of a "line of divergence" in the cross-shelf flow or the offshore increase in the magnitude of the longshore velocity, were reproduced by his model.…”
Section: Driving Mechanism: Earlier Theoriesmentioning
confidence: 97%
“…Early investigations (e.g., Scott and Csanady, 1976) pointed out that tidally driven fluctuations hinder the analysis of the wind-induced fluctuations over relatively shallow depths, where the frictional adjustment time may be similar or shorter than the tidal period. In these environments, for typical wind events, the wind-forcing, tidal and frictional periods are all comparable; in particular, the semidiurnal and frictional times become similar at depths of about 60 m (Csanady, 1982).…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%